Identifying factors affecting willingness to participate in floating population health volunteer services by Chinese volunteers based on the theory of the planned behavior expansion model - Wu, Wei-ling; Yu, Hai-Yan; Zhou, Hai-Xia (Frontiers in Psychology, 2022)
China has the world’s largest internal migrant population, called the floating population. Compared to local residents, the floating population utilizes different health services and relies heavily on health volunteer services for supplementary services. In this study, the theory of planned behavior (TPB) model was used to study the willingness of volunteers to participate in floating population health volunteer services. We examined the effects of several factors on willingness to participate and found that attitude and subjective norm, but not perceived behavioral control, have significant predictive effects on willingness to participate in health volunteer services. Furthermore, altruistic values, social incentives, and personality traits all have significant predictive effects on volunteer participation, but also indirectly affect willingness through attitude and subjective norm. These findings help us understand what factors affect volunteers’ willingness to provide health services to the floating population and have important implications for mobilizing volunteers in floating population health services.